The effect of the Kelp 40 seaweed extract on the growth and vegetation value of two cultivars of wheat - Abdulaziz Shekho Abduljabbar (مجلة التربية والعلم, 2013)
Abstract The effect of spraying Shoot groups of two wheat cultivars (Um Rabee and Sham 6) by different Seaweed extract (Kelp 40) concentrations of (0.0, 2.0, 4.0) ml/L at three different growing times on the growth and vegetation value of these plants growing under plastic house condition was investigated. Results showed that there was a significant increase in leaf surface area, chlorophyll a and b concentration in leaf tissues and carbohydrate, Ca, Mg, K in the grain treated with (4.0)ml/L seaweed extract, while the Length plant and protein concentration was not significantly different. The treatment with (2.0)ml/L extract showed a significant increase in chlorophyll b concentration in leaf tissues and carbohydrate, Ca, K in the grain and a non-significant increase in the length of the plant, leaf surface area, chlorophyll a, protein, K concentration in grains of the wheat plant in comparison with control. It has been result showed that the spraying of the Shoot groups with the extract of the concentration of (4.0) ml/L leads to a significant increase in the length of plant, leaf surface area, chlorophyll a and b concentration in leaf tissues and K concentration of the grain in the cultivars (Sham 6). On the other hand using the same concentration of the extract concerning the cultivars (Um Rabee) there has been a significant increase in the concentration of carbohydrate, Ca and Mg. The cultivated Sham 6 dominated the cultivated Um Rabee in most parameters.